Challenges and Solutions in Ethnographic Research Ethnography with a Twist - Lähdesmäki, Tuuli; Koskinen-Koivisto, Eerika; Čeginskas, Viktorija L.A; Koistinen, Aino-Kaisa (Taylor & Francis, 2021)
Challenges and Solutions in Ethnographic Research: Ethnography with a Twist seeks to rethink ethnography 'outside the box' of its previous tradition and to develop ethnographic methods by critically discussing the process, ethics, impact and knowledge production in ethnographic research. This interdisciplinary edited volume argues for a 'twist' that supports openness, courage, and creativity to develop and test innovative and unconventional ways of thinking and doing ethnography. 'Ethnography with a twist' means both an intentional aim to conduct ethnographic research with novel approaches and methods but also sensitivity to recognize and creativity to utilize different kinds of 'twist moments' that ethnographic research may create for the researcher.　 This edited volume critically evaluates new and old methodological tools and their ability to engage with questions of power difference. It proposes new collaborative methods that allow for co-production and co-creation of research material as well as shared conceptual work and wider distribution of knowledge. The book will be of use to ethnographers in humanities and social science disciplines including sociology, anthropology and communication studies.